(untitled) (Educational Dimension, 2020)
The article is devoted to the problem of didactization of linguistic and historical materials about the activities of German immigrants in the territory of Kyiv. The main focus is on the choice and justification of the types of tasks for using these materials during German classes. It is determined that semi-open and open types of tasks are optimal in the process of didactization of these materials. A number of tasks have been developed on the basis of materials on the contribution of German architects to the design and construction of recognized architectural monuments of Kyiv. It has been found that the proposed assignments are appropriate to use for students at B1 + level in accordance with the Common European Guidelines for Language Education. The developed tasks are based on the following principles: communicative orientation, activity orientation, intercultural sensitization, and scaffolding.